2017
DOI: 10.5194/bg-14-3067-2017
|View full text |Cite
|
Sign up to set email alerts
|

Benthic foraminiferal Mn / Ca ratios reflect microhabitat preferences

Abstract: Abstract. The Mn / Ca of calcium carbonate tests of living (rose-Bengal-stained) benthic foraminifera (Elphidium batialis, Uvigerina spp., Bolivina spissa, Nonionellina labradorica and Chilostomellina fimbriata) were determined in relation to pore water manganese (Mn) concentrations for the first time along a bottom water oxygen gradient across the continental slope along the NE Japan margin (western Pacific). The local bottom water oxygen (BWO) gradient differs from previous field study sites focusing on fora… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 49 publications
3
37
1
Order By: Relevance
“…This latter difference can be explained by the much higher pore water Mn 2+ concentrations in our study (< 310 µmol L −1 ) and in the study of Koho et al (2017; < 5 µmol L −1 ) compared to the study of Glock et al (2012;< 0.1 µmol L −1 ). Despite the different pore water Mn 2+ concentrations in our study compared to Koho et al (2017), we found rather similar foraminiferal Mn/Ca ratios, and this contrast could be partly resolved by higher partition coefficients in deep-sea species compared to coastal species (Barras et al, 2018). For A. tepida, the range measured in specimens from Lake Grevelingen in our study compares well with measured average Mn/Ca ratios in the study of Barras et al (2018;0.13 and 0.86 mmol mol −1 ) for a similar range of pore water Mn 2+ concentrations compared to the concentration of dissolved Mn in the seawater of the culturing experiments (10 to 100 µmol L −1 ).…”
Section: Ontogenetic Trends Of Mn/ca Ratioscontrasting
confidence: 72%
See 4 more Smart Citations
“…This latter difference can be explained by the much higher pore water Mn 2+ concentrations in our study (< 310 µmol L −1 ) and in the study of Koho et al (2017; < 5 µmol L −1 ) compared to the study of Glock et al (2012;< 0.1 µmol L −1 ). Despite the different pore water Mn 2+ concentrations in our study compared to Koho et al (2017), we found rather similar foraminiferal Mn/Ca ratios, and this contrast could be partly resolved by higher partition coefficients in deep-sea species compared to coastal species (Barras et al, 2018). For A. tepida, the range measured in specimens from Lake Grevelingen in our study compares well with measured average Mn/Ca ratios in the study of Barras et al (2018;0.13 and 0.86 mmol mol −1 ) for a similar range of pore water Mn 2+ concentrations compared to the concentration of dissolved Mn in the seawater of the culturing experiments (10 to 100 µmol L −1 ).…”
Section: Ontogenetic Trends Of Mn/ca Ratioscontrasting
confidence: 72%
“…These studies show that benthic foraminifera register environmental Mn 2+ concentrations in their tests (Reichart et al, 2003;Munsel et al, 2010;Glock et al, 2012;Groeneveld and Filipsson, 2013;Koho et al, 2015Koho et al, , 2017McKay et al, 2015;Barras et al, 2018). For example, Koho et al (2015Koho et al ( , 2017 demonstrated that foraminiferal species occupying a relatively deep microhabitat display higher Mn/Ca ratios than those living near the sediment surface. Furthermore, by using microanalytical techniques, capable of measuring elemental concentrations in single foraminiferal chambers, short-term variability in oxygenation may be unravelled.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations